Constitutive modelling and springback prediction for creep age forming of 2124 aluminium alloy. (1st September 2013) - Xu, X L; Zhan, L H; Li, Y G; Huang, M H
Abstract : In order to improve the mechanical properties and reduce fabrication cost of large sheet metal parts, creep age forming (CAF) technology was developed, which is a process combined creep forming and heat treatment together. Springback of the workpiece in CAF is directly related to process parameters, such as, aging time, experimental stress and temperature. The aim of this paper is to establish a set of creep constitutive model, which can accurately predict the springback of 2124 aluminium alloy in CAF. A series of creep tests were carried out under different stress levels as 200, 225 and 250 MPa, and different temperatures as 185, 190 and 195°C for the solid solution treated and quenched 2124 aluminium alloy. Based on creep test data, a set of classic creep constitutive equations were established. Some important conclusions were drawn: the fitting curves of the constitutive equations could describe the test data in a good way; the creep strain increases with the increasing aging time, temperature and experimental stress. Then the springback of 2124 aluminium alloy during CAF process were analyzed by the finite element software MSC.Marc. Comparisons between the experiment analyses and finite element models show good correlation, and approve the forecast capability of FEM simulation for springback after CAF. At the end, the influence of process parameters on springback is studied, which provides essential foundation for designer to evaluate scheme and to optimise tool system design.